The effect of preferred music on mood and performance in a high-cognitive demand occupation. - Lesiuk, Teresa (Journal of Music Therapy)
Mild positive affect has been shown in the psychological literature to improve cognitive skills of creative problem-solving and systematic thinking. Individual preferred music listening offers opportunity for improved positive affect. The purpose of this study was to examine the effect of preferred music listening on state-mood and cognitive performance in a high-cognitive demand occupation. Twenty-four professional computer information systems developers (CISD) from a North American IT company participated in a 3-week study with a music/no music/music weekly design. During the music weeks, participants listened to their preferred music "when they wanted, as they wanted." Self-reports of State Positive Affect, State Negative Affect, and Cognitive Performance were measured throughout the 3 weeks. Results indicate a statistically significant improvement in both state-mood and cognitive performance scores. "High-cognitive demand" is a relative term given that challenges presented to individuals may occur on a cognitive continuum from need for focus and selective attention to systematic analysis and creative problem-solving. The findings and recommendations have important implications for music therapists in their knowledge of the effect of music on emotion and cognition, and, as well, have important implications for music therapy consultation to organizations.